2017
DOI: 10.1007/s40119-017-0102-x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Complications of Marijuana and Related Substances: A Review

Abstract: The recreational use of cannabis has sharply increased in recent years in parallel with its legalization and decriminalization in several countries. Commonly, the traditional cannabis has been replaced by potent synthetic cannabinoids and cannabimimetics in various forms. Despite overwhelming public perception of the safety of these substances, an increasing number of serious cardiovascular adverse events have been reported in temporal relation to recreational cannabis use. These have included sudden cardiac d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
135
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(152 citation statements)
references
References 122 publications
(139 reference statements)
4
135
0
3
Order By: Relevance
“…Pathway enrichment revealed that hypermethylation in cannabis-only users was overrepresented in genes associated with cardiomyopathies and neural signalling. This is consistent with the literature which raises clinical concerns around cardiac complications potentially associated with cannabis use 100103 . The enrichment of genes associated with neural signalling pathways is also consistent with the literature, including previous analyses of the CHDS cohort, which report associations between cannabis exposure and brain related biology such as mood disorders 7; 12; 48; 49; 5154; 104; 105 .…”
Section: Discussionsupporting
confidence: 92%
“…Pathway enrichment revealed that hypermethylation in cannabis-only users was overrepresented in genes associated with cardiomyopathies and neural signalling. This is consistent with the literature which raises clinical concerns around cardiac complications potentially associated with cannabis use 100103 . The enrichment of genes associated with neural signalling pathways is also consistent with the literature, including previous analyses of the CHDS cohort, which report associations between cannabis exposure and brain related biology such as mood disorders 7; 12; 48; 49; 5154; 104; 105 .…”
Section: Discussionsupporting
confidence: 92%
“…Although a meta-analysis of epidemiologic studies published between 1960 and 2010 showed that risk of AMI in cannabis user is low [31], a recent systemic literature review shows that the younger patients presenting with AMI following cannabis use had no preexisting coronary artery disease have had normal coronary angiograms [32], had toxicology positive for cannabis only, suggesting there may be a presence of potent synthetic cannabis increasing the overall risk of AMI attributable to cannabis [33]. There are studies that have shown that immediate risk of AMI increases fivefold within an hour of cannabis exposure compared with nonusers [15], and the annual risk of AMI in daily cannabis users may increase by 3% per year [34]. Our study, along with past literature [1,15,31e33,35], shows the magnitude of cannabis abuse/dependence to be at a higher scale as a causative factor for AMI, compared with other drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Recreational drugs tend to have varying harmful effects on the cardiovascular system. Reported adverse cardiovascular events associated with cannabis, synthetic cannabinoids, and cannabimimetics include, but are not limited to, acute coronary syndrome, cerebrovascular diseases including stroke and vasospasm, rhythm disturbances, vasculopathy, and rhabdomyolysis [15]. While considering the mechanisms that are involved with cannabis and related drugs, it is vital to note that the molecules present in cannabis can change the metabolism of other drugs because of their natural tendency to clear metabolic pathways such as cytochromes CYP450 [16].…”
mentioning
confidence: 99%
“…Oxygen demand-supply mismatch contributing to myocardial ischemia is due to decreased oxygen supply from elevated levels of carboxyhemolgobin, nearly five times higher than seen in tobacco cigarettes, generated from inhalation of combustion products [8,9,21,27]. Cannabis derived reactive oxygen species, CBR1 mediated endothelial dysfunction, and regional arterial vasospasm cause ischemia and increase the risk for subtotal to total arterial occlusion and downstream infarction [28,29]. The cannabinoid vasoactive effect ranges from vasoconstriction to vasodilatation in different vascular beds, with the coronary arterial bed likewise demonstrating both vasoconstriction and vasodilation [7,30].…”
Section: Discussionmentioning
confidence: 99%